Optimalisasi Repositori Institusi IAIN Curup sebagai Sarana Komunikasi Ilmiah Kampus - Okky Rizkyantha; Muksal Mina Putra; Habiburrahman Habiburrahman (Tik Ilmeu : Jurnal Ilmu Perpustakaan dan Informasi, 2022)
The existence of institutional repository become one of strategy of institute’s tridharma. Besides accelerating the dissemination of information to both internal and external users, repository has become a necessity for the development of a scientific atmosphere in universities.  The purpose of this article is to find out how to optimize the IAIN Curup institutional repository and increase scientific productivity. This article uses a qualitative method as the research method. The data collection process was carried out through 3 methods, they are observation, interviews and documentation. The data analysis technique uses 3 methods, namely data reduction, data display, and verification. This article found that Institutional repository IAIN Curup has roles such as (1) Scientific Information Preservation, (2) public visibility and improvement of webometrics, (3) ease of dissemination of scientific information. IAIN Curup Library has done many things to optimize the use of institutional repository such as (1) making e-resources guidelines, (2) Promoting Institutional repository through various media and activities, (3) coordinating with faculties